Formal help-seeking among community-based Czech individuals with sexual interest in minors is associated with the perceived urgency of self-identified concerns - Martinec Nováková, Lenka; Krejčová, Lucie; Bártová, Klára; Androvičová, Renáta; Klapilová, Kateřina (Frontiers in Psychology, 2025)
BackgroundIn the community, there are non-forensic individuals who experience sexual interest in minors and have specific mental health needs and concerns. If left unaddressed, these issues may contribute to problematic sexual behaviors. Although supportive treatment programs are emerging in Czechia, self-motivated help-seeking remains generally low in this at-risk population.ObjectiveTo inform strategies for encouraging preventive service use, this study aimed to examine how past help-seeking experiences relate to factors that may influence the likelihood of seeking professional help, as identified in the literature.MethodsAn online survey was conducted with a purposive sample of 97 community-based, predominantly male, non-forensic adults whose responses to hypothetical scenarios suggested a sexual interest in minors. The study investigated the relationship between self-reported past formal help-seeking behavior (any vs. none) and two key variables: perceived urgency of self-identified concerns and dismissive attitudes toward professional assistance. Analyses controlled for other forms of support sought.ResultsFormal support sources were rarely approached. A significant association was found between low perceived urgency of self-identified concerns and the absence of formal help-seeking behavior (β = 0.33, F(1) = 6.34, p = 0.014).ConclusionTo promote professional service uptake among this difficult-to-reach population, it is essential to enhance mental health literacy across the broader community and to educate individuals about the role of psychological well-being in preventing problematic behaviors.